Affordable headphones for accessible screening audiometry : an evaluation of the Sennheiser HD202 II Supra-aural headphone - Swanepoel, De Wet (University of Pretoria, 2017)
Dissertation (M Communication Pathology)--University of Pretoria, 2017.